2016
DOI: 10.1587/transinf.2015edp7197
|View full text |Cite
|
Sign up to set email alerts
|

Quickly Converging Renumbering in Network with Hierarchical Link-State Routing Protocol

Abstract: SUMMARYWe have developed an automatic network configuration technology for flexible and robust network construction. In this paper, we propose a two-or-more-level hierarchical link-state routing protocol in Hierarchical QoS Link Information Protocol (HQLIP). The hierarchical routing easily scales up the network by combining and stacking configured networks. HQLIP is designed not to recompute shortest-path trees from topology information in order to achieve a high-speed convergence of forwarding information bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Hu and Krishnamachari [61] proposed a throughput optimized task scheduler, targeting applications (such as computer vision and video processing) where input data are continuously and steadily fed into the execution pipeline for DCOMP to perform computation on the edge leading to significant reduction in communication with the remote cloud. Fujikawa et al [62] described DCOMP as a new vision of joint computation and communication resource [64] designed a runtime scheduling software tool for DCOMP, which can deploy pipelined computations described in the form of a Directed Acyclic Graph (DAG) on multiple geographically dispersed compute nodes at the edge and in the cloud. Nguyen et al [65] studied file transfer times between geographically dispersed cloud computing points using SCP (secure copy) and demonstrated via a set of real-world measurement experiments that the end-to-end file transfer time in a dispersed computing environment can be modelled as a quadratic function of the file size.…”
Section: The Features and Visions Of Dcompmentioning
confidence: 99%
See 1 more Smart Citation
“…Hu and Krishnamachari [61] proposed a throughput optimized task scheduler, targeting applications (such as computer vision and video processing) where input data are continuously and steadily fed into the execution pipeline for DCOMP to perform computation on the edge leading to significant reduction in communication with the remote cloud. Fujikawa et al [62] described DCOMP as a new vision of joint computation and communication resource [64] designed a runtime scheduling software tool for DCOMP, which can deploy pipelined computations described in the form of a Directed Acyclic Graph (DAG) on multiple geographically dispersed compute nodes at the edge and in the cloud. Nguyen et al [65] studied file transfer times between geographically dispersed cloud computing points using SCP (secure copy) and demonstrated via a set of real-world measurement experiments that the end-to-end file transfer time in a dispersed computing environment can be modelled as a quadratic function of the file size.…”
Section: The Features and Visions Of Dcompmentioning
confidence: 99%
“…A hierarchical routing protocol needs a complex cluster head election algorithm, and the cluster heads are easy to become the bottleneck of the network for the reason of most of data forwarded by cluster heads. The typical hierarchical routing protocols include CGSR (Cluster-head Gateway Switch Routing Protocol), HSR (Hierarchical State Routing Protocol) [62], LANMAR (Landmark Ad Hoc Routing Protocol) [72], etc., and the common table-driven routing protocols are DSDV (Destination-Sequenced Distance Vector) [73], WRP (Wireless Routing Protocol) [74], OLSR (Optimized Link State Routing) [75], AODV (Ad hoc On-demand Distance Vector Routing) [76], etc. It can be found that there are multiple routing protocols used in the current MANET, and different types of protocols have different mechanisms with their own characteristics and different environmental adaptabilities.…”
Section: Routing Protocol and Forwarding Control Of Danetmentioning
confidence: 99%
“…For automatic IPv6 address allocation and assignment to their interfaces, we use Hierarchical/Automatic Number Allocation (HANA) protocol [18]. For automatic FIB set up, we use a link-state routing protocol Hierarchical QoS Link Routing Protocol (HQLIP) [19]. Each vnn.rb starts HANA/HQLIP protocol software on each physical node.…”
Section: Developed Program Modulesmentioning
confidence: 99%